Quantification of lipid-rich core in carotid atherosclerosis using magnetic resonance T2 mapping: relation to clinical presentation - Chai, J; Biasiolli, L; Li, L; Alkhalil, M; Galassi, F; Darby, C; Halliday, A; Hands, L; Magee, T; Perkins, J; Sideso, E; Handa, A; et al. (Elsevier, 2016)
OBJECTIVES: The aim of this study was to: 1) provide tissue validation of quantitative T2 mapping to measure plaque lipid content; and 2) investigate whether this technique could discern differences in plaque characteristics between symptom-related and non–symptom-related carotid plaques. BACKGROUND: Noninvasive plaque lipid quantification is appealing both for stratification in treatment selection and as a possible predictor of future plaque rupture. However, current cardiovascular magnetic resonance (CMR) methods are insensitive, require a coalesced mass of lipid core, and rely on multicontrast acquisition with contrast media and extensive post-processing. METHODS: Patients scheduled for carotid endarterectomy were recruited for 3-T carotid CMR before surgery. Lipid area was derived from segmented T2 maps and compared directly to plaque lipid defined by histology. RESULTS: Lipid area (%) on T2 mapping and histology showed excellent correlation, both by individual slices (R = 0.85, p < 0.001) and plaque average (R = 0.83, p < 0.001). Lipid area (%) on T2 maps was significantly higher in symptomatic compared with asymptomatic plaques (31.5 +/- 3.7% vs. 15.8 +/- 3.1%; p = 0.005) despite similar degrees of carotid stenosis and only modest difference in plaque volume (128.0 +/- 6.0 mm3 symptomatic vs. 105.6 +/- 9.4 mm3 asymptomatic; p = 0.04). Receiver-operating characteristic analysis showed that T2 mapping has a good ability to discriminate between symptomatic and asymptomatic plaques with 67% sensitivity and 91% specificity (area under the curve: 0.79; p = 0.012). CONCLUSIONS: CMR T2 mapping distinguishes different plaque components and accurately quantifies plaque lipid content noninvasively. Compared with asymptomatic plaques, greater lipid content was found in symptomatic plaques despite similar degree of luminal stenosis and only modest difference in plaque volumes. This new technique may find a role in determining optimum treatment (e.g., providing an indication for intensive lipid lowering or by informing decisions of stents vs. surgery).